The Influence of Usefulness, Ease of Use, and Trust on E-Commerce Use Intention Mediated by Attitude - Ernawati, Sri; Sanaji, Sanaji; Andjarwati, Anik Lestari (Jambura Science of Management, 2025)
Purpose: This study aims to investigate the influence of perceived usefulness, perceived ease of use, and trust on the intention to use e-commerce applications, specifically in the context of post-pandemic consumer behavior. By introducing attitude as a mediating variable, the research seeks to uncover the psychological pathway through which these perceptual factors shape user intentions. Furthermore, the study addresses a contextual gap by focusing on users in West Nusa Tenggara, contributing to a more localized understanding of e-commerce adoption in emerging regions.Design/Methodology/Approach: This study adopts a quantitative research design employing an explanatory survey approach, which entails gathering data directly from respondents. The primary research tool is a questionnaire based on a Likert scale, comprising a series of structured questions for participants to respond to. The study sample includes 100 participants, selected through purposive sampling. To examine both the direct and indirect relationships among the research variables, data analysis is performed using Structural Equation Modeling (SEM) with the aid of SmartPLS software.Findings: The results of the study show that the perceived ease of use and perceived trust have a direct and significant influence on the intention to use e-commerce shoppe applications, while perceived usefulness does not have a direct effect but significantly contributes to shaping users’ attitudes. Attitude is proven to be a strong mediating variable that bridges the relationship between users’ perceptions (usefulness, ease of use, and trust) and their intention to use.